A water-based coating for soft stone surface spraying and preparation method thereof
By using water-based coatings polymerized by dienyl quaternary ammonium fluorosiloxane and acrylic monomers on the surface of soft stone, the problem of mold in soft stone materials in humid environments is solved, the waterproof and antibacterial properties are improved, and the waterproof and antibacterial properties are extended. The service life is achieved and environmentally friendly coating applications are achieved.
Patent Information
- Application Number
- CN202410695450.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-31
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-05-31
AI Technical Summary
Existing soft stone materials are prone to mildew in humid environments, resulting in unclear and beautiful texture on the surface, limiting their further development and application.
Using a preparation method of water-based coating for surface spraying of soft stone, the polymerization of dienyl quaternary ammonium salt fluoro-containing silicone with acrylic monomer, and the addition of defoaming agents and other additives to form an antibacterial and anti-mold acrylic resin coating. Courses are carried out in combination with spraying process.
It significantly improves the waterproof and antibacterial properties of soft stone surfaces, extends service life, and realizes green and environmentally friendly coating applications.
Smart Images

Figure BDA0004869569640000021 
Figure BDA0004869569640000031 
Figure BDA0004869569640000032
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, in particular to a water-based coating for spraying on a soft stone surface and a preparation method thereof. Background Art
[0002] Soft stone is a flexible imitation stone material with an inorganic material as the base material and an environmentally friendly water-soluble architectural coating added. It has good flexibility, is thin and light, and can meet the design requirements of buildings of different shapes. As a new type of interior and exterior wall building material with imitation stone effect, soft stone can not only present a realistic stone effect, but also has advantages in cost and construction efficiency. However, the existing soft stone material is prone to mildew in a humid environment, making the perfect pattern and texture on its surface unclear and unsightly, which greatly limits the further development and application of soft stone materials. Therefore, it has become an urgent problem to prepare an antibacterial, mildew-proof and water-resistant water-based coating for spraying on the surface of soft stone.
[0003] The paint for spraying on the surface of soft stone can decorate and protect the soft stone, make the building wall beautiful and tidy, and also protect the building wall, which helps to extend the service life of the wall; therefore, environmentally friendly water-based paint is becoming more and more popular; water-based acrylic resin is a non-toxic and non-flammable environmentally friendly material, which is widely used in the fields of coatings, adhesives, etc.; since traditional water-based acrylic resins are mostly chain-like linear structures, they have poor water resistance and stain resistance, and need to be further modified; Chinese patent CN117777807A discloses a high-performance, low-cost microcrystalline stone paint and a preparation method thereof, which is based on polysiloxane and gives an acrylic matrix significant weather resistance and waterproof properties. The prepared paint is a water-based paint, which has less organic volatility than solvent-based paint, less environmental pollution, and is green and environmentally friendly. It has important application value in the field of building coatings, especially in the field of imitation stone paint; however, it does not significantly improve the water and stain resistance.
[0004] Improving the antibacterial and mildew-proof properties of acrylic resin is beneficial to improving the antibacterial and mildew-proof properties of furniture building materials and wall decoration materials; Chinese patent CN105199577B discloses an antibacterial low surface energy marine antifouling coating composition, and the quaternary ammonium salt-modified polyhydroxy fluorine-containing acrylic resin has both the low surface energy of organic fluorine and organic silicon polymers and the antibacterial properties of quaternary ammonium salts, and can be widely used in the field of marine antifouling and construction materials; the novel diene quaternary ammonium salt fluorine-containing siloxane monomer synthesized by the present invention is polymerized with acrylic monomers to prepare waterproof and antibacterial acrylic resin, which has broad application prospects in the fields of construction materials, antibacterial coatings, etc. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art, provide a water-based paint for spraying on the surface of soft stone and a preparation method thereof, solve the problem that the surface of the existing soft stone is prone to mildew, and improve the waterproof and antibacterial properties of the soft stone.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A method for preparing a water-based coating for spraying on a soft stone surface comprises the following steps:
[0008] (1) Under nitrogen atmosphere, bis(3-bromoacetamide-5-trifluoromethylphenyl)siloxane, sodium iodide and acetonitrile are added to a reaction flask, and potassium carbonate and N,N-dimethylallylamine are added after stirring evenly. The reaction is stirred and filtered after the reaction is completed, and the filtrate is washed with ethyl acetate. The filtrate is concentrated and dried to obtain a divinyl quaternary ammonium salt fluorinated siloxane. The preparation reaction formula is as follows:
[0009]
[0010] (2) Under nitrogen atmosphere, deionized water, 3-5 g initiator ammonium persulfate, 5-8 g emulsifier sodium dodecylbenzene sulfonate, and 2-3 g OP-10 were added to a reaction bottle equipped with a dropping funnel, and stirred to dissolve; a mixed solution of 100 g glycidyl methacrylate, 15-20 g ethyl acrylate, 50-70 g butyl acrylate, 30-40 g methacrylic acid, and 3-15 g diene quaternary ammonium salt fluorinated silicone was added to the dropping funnel after mixing, 1 / 3 of the mixed solution was first added dropwise, and the mixture was reacted at 65-75° C. for 1-3 h, and then the remaining mixed solution was added dropwise, and the reaction was continued at the same temperature for 2-4 h. After the reaction was completed, ammonia water was added for neutralization, and finally 0.2-0.6 g defoamer, 0.1-0.3 g wetting dispersant, and 0.05-0.2 g leveling agent were added to obtain a water-based coating for soft stone surface spraying.
[0011] Furthermore, in step (1), the ratio of bis(3-bromoacetamide-5-trifluoromethylphenyl)siloxane, sodium iodide, potassium carbonate and N,N-dimethylallylamine is 1 mol:(0.5-0.8) mol:(3-4.5) mol:(2.1-2.4) mol.
[0012] Furthermore, in step (1), the reaction temperature is 60-80°C and the reaction time is 16-32h.
[0013] Furthermore, the preparation method of bis(3-bromoacetamide-5-trifluoromethylphenyl)siloxane in step (1) comprises the following steps:
[0014] S1. Under a nitrogen atmosphere, add dichlorodimethylsilane and toluene to a reaction flask, stir evenly, then add 3-nitro-5-(trifluoromethyl)phenol and sodium hydride, stir to react, and after the reaction is completed, cool to room temperature, filter, and recrystallize from toluene and n-hexane to obtain bis(3-nitro-5-trifluoromethylphenyl)siloxane.
[0015] S2. In a hydrogen atmosphere, add bis(3-nitro-5-trifluoromethylphenyl)siloxane and ethyl acetate to a reaction flask, stir evenly, add 10% Pd / C by mass, react at 40-60°C for 5-12h, filter, wash with ethyl acetate, and concentrate under reduced pressure to obtain bis(3-amino-5-trifluoromethylphenyl)siloxane. The preparation reaction formula is as follows:
[0016]
[0017] S3. Under nitrogen atmosphere, add bromoacetic acid, HATU and N,N-dimethylformamide to the reaction flask, stir evenly, add bis(3-amino-5-trifluoromethylphenyl)siloxane and triethylamine, react at 20-35°C for 12-24h, add ethyl acetate and deionized water for extraction, concentrate the organic phase, and dry to obtain bis(3-bromoacetamide-5-trifluoromethylphenyl)siloxane. The preparation reaction formula is as follows:
[0018]
[0019] Furthermore, in step S1, the ratio of dichlorodimethylsilane, 3-nitro-5-(trifluoromethyl)phenol, and sodium hydride is 1 mol:(2.05-2.2) mol:(2.3-2.5) mol.
[0020] Furthermore, in step S1, the reaction temperature is 80-100° C., and the reaction time is 2-5 h.
[0021] Furthermore, in step S2, the ratio of bis(3-nitro-5-trifluoromethylphenyl)siloxane to Pd / C is 1 mol:(0.01-0.03) mol.
[0022] Furthermore, in step S3, the ratio of bromoacetic acid, HATU, bis(3-amino-5-trifluoromethylphenyl)siloxane and triethylamine is (2.1-2.3) mol: (2.8-3.2) mol: 1 mol: (3.5-4) mol.
[0023] Furthermore, the spraying process is: soft stone degreasing - alcohol washing - water washing - sandblasting - spraying water-based paint - curing.
[0024] Furthermore, the curing temperature is 70-90°C.
[0025] By adopting the above technical solution, the beneficial effects of the present invention are:
[0026] Bis(3-nitro-5-trifluoromethylphenyl)siloxane was synthesized by reacting dichlorodimethylsilane with 3-nitro-5-(trifluoromethyl)phenol, and then subjected to nitro reduction reaction with Pd / C in a hydrogen atmosphere to obtain bis(3-amino-5-trifluoromethylphenyl)siloxane, which was then reacted with bromoacetic acid and N,N-dimethylallylamine in sequence to obtain a bis-alkenyl quaternary ammonium salt fluorinated siloxane, which was finally polymerized with acrylic monomers and additives such as a defoaming agent were added to obtain a water-based coating for spraying on soft stone surfaces. The preparation method is novel and efficient, and the reaction conditions are mild.
[0027] The quaternary ammonium group contained in the diene quaternary ammonium salt fluorinated siloxane mainly plays a bactericidal role. It can be adsorbed on the surface of Escherichia coli, penetrate the cell wall, and then combine with the cell membrane, changing the permeability of the Escherichia coli cell membrane, causing the substances in the bacteria to leak out, and finally killing the Escherichia coli, thereby achieving the purpose of antibacterial and mildew prevention; organic fluorine, silicon and other low surface energy substances are introduced into the water-based paint. The bond energy of CF and Si-O bonds is greater than that of CH and CO, and the atomic electron cloud has a stronger shielding effect on CC bonds than H atoms. It is difficult for water molecules to penetrate and a Si-O-Si three-dimensional cross-linked network structure is formed on the surface of the paint, so that the prepared composite material has low surface free energy. At the same time, a very thin molecular layer can be formed on the surface of the material, thereby reducing the surface energy, making it impossible for water droplets to stay on the surface, thereby achieving a waterproof effect.
[0028] The acrylic resin coating is obtained by polymerizing the fluorinated silicone of the diolefin quaternary ammonium salt with acrylic monomers. The hydrophobic organic silicon fluorine group and the antibacterial diquaternary ammonium salt group are introduced into the main chain of the acrylic resin, thereby improving the water resistance and waterproofness of the acrylic resin coating, and at the same time giving the water-based coating excellent antibacterial and mildew-proof effects, thereby broadening its application fields in furniture and building materials, wall decoration and protection, etc. The water-based coating prepared by the invention can be sprayed on the surface of the soft stone through the process of soft stone degreasing-alcohol washing-water washing-sandblasting-spraying water-based coating-curing, and has antibacterial and mildew-proof, water-resistant performance, no VOC emission, and is green and environmentally friendly. DETAILED DESCRIPTION
[0029] In order to enable those skilled in the art to better understand the present application, the technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the specific embodiments in the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work should fall within the scope of protection of the present application.
[0030] 3-Nitro-5-(trifluoromethyl)phenol, CAS number is 349-57-5.
[0031] HATU, CAS number is 148893-10-1.
[0032] N,N-dimethylallylamine, CAS number is 2155-94-4.
[0033] Example 1
[0034] (1) Under nitrogen atmosphere, 20 mmol of dichlorodimethylsilane and 160 mL of toluene were added to a reaction flask. After stirring, 42 mmol of 3-nitro-5-(trifluoromethyl)phenol and 48 mmol of sodium hydride were added. The mixture was reacted at 90° C. for 3 h. The mixture was cooled to room temperature, filtered, and recrystallized from toluene and n-hexane to obtain bis(3-nitro-5-trifluoromethylphenyl)siloxane.
[0035] (2) Under a hydrogen atmosphere, 18 mmol of bis(3-nitro-5-trifluoromethylphenyl)siloxane and 235 mL of ethyl acetate were added to a reaction flask. After stirring evenly, 0.36 mmol of 10% Pd / C was added. The mixture was reacted at 50° C. for 10 h. The mixture was filtered, washed with ethyl acetate, and concentrated under reduced pressure to obtain bis(3-amino-5-trifluoromethylphenyl)siloxane.
[0036] (3) Under nitrogen atmosphere, 33 mmol of bromoacetic acid, 45 mmol of HATU and 150 mL of N,N-dimethylformamide were added to the reaction flask, and after stirring, 15 mmol of bis(3-amino-5-trifluoromethylphenyl)siloxane and 57 mmol of triethylamine were added, and the mixture was reacted at 25° C. for 16 h. Ethyl acetate and deionized water were added for extraction, and the organic phase was concentrated and dried to obtain bis(3-bromoacetamide-5-trifluoromethylphenyl)siloxane.
[0037] (4) Under nitrogen atmosphere, 12 mmol of bis(3-bromoacetamide-5-trifluoromethylphenyl)siloxane, 7.8 mmol of sodium iodide and 200 mL of acetonitrile were added to a reaction flask, and after stirring, 42 mmol of potassium carbonate and 27 mmol of N,N-dimethylallylamine were added. The mixture was reacted at 70° C. for 24 h, filtered, washed with ethyl acetate, and the filtrate was concentrated and dried to obtain a divinyl quaternary ammonium salt fluorinated siloxane.
[0038] (5) Under nitrogen atmosphere, deionized water, 4 g initiator ammonium persulfate, 6 g emulsifier sodium dodecylbenzene sulfonate, and 2.5 g OP-10 were added to a reaction bottle equipped with a dropping funnel and stirred to dissolve; a mixed solution of 100 g glycidyl methacrylate, 18 g ethyl acrylate, 60 g butyl acrylate, 35 g methacrylic acid, and 3 g diene quaternary ammonium salt fluorinated silicone was added to the dropping funnel after mixing, 1 / 3 of the mixed solution was first added dropwise, and the mixture was reacted at 70° C. for 2 h, and then the remaining mixed solution was added dropwise, and the reaction was continued at the same temperature for 3 h. After the reaction was completed, ammonia water was added for neutralization, and finally 0.3 g defoamer BYK-012, 0.2 g wetting dispersant BYK-190, and 0.01 g leveling agent TEGO-A115 were added to obtain a water-based coating for soft stone surface spraying.
[0039] Example 2
[0040] (1) Under nitrogen atmosphere, 45 mmol of dichlorodimethylsilane and 225 mL of toluene were added to a reaction flask. After stirring, 92.25 mmol of 3-nitro-5-(trifluoromethyl)phenol and 103.5 mmol of sodium hydride were added. The mixture was reacted at 100° C. for 2 h. The mixture was cooled to room temperature, filtered, and recrystallized from toluene and n-hexane to obtain bis(3-nitro-5-trifluoromethylphenyl)siloxane.
[0041] (2) Under a hydrogen atmosphere, 40 mmol of bis(3-nitro-5-trifluoromethylphenyl)siloxane and 400 mL of ethyl acetate were added to a reaction flask, stirred evenly, and then 4 mmol of 10% Pd / C was added. The mixture was reacted at 60° C. for 5 h, filtered, washed with ethyl acetate, and concentrated under reduced pressure to obtain bis(3-amino-5-trifluoromethylphenyl)siloxane.
[0042] (3) Under nitrogen atmosphere, 73.5 mmol of bromoacetic acid, 98 mmol of HATU and 280 mL of N,N-dimethylformamide were added to the reaction flask, and after stirring, 35 mmol of bis(3-amino-5-trifluoromethylphenyl)siloxane and 122.5 mmol of triethylamine were added, and the mixture was reacted at 35° C. for 12 h. Ethyl acetate and deionized water were added for extraction, and the organic phase was concentrated and dried to obtain bis(3-bromoacetamide-5-trifluoromethylphenyl)siloxane.
[0043] (4) Under nitrogen atmosphere, 25 mmol of bis(3-bromoacetamide-5-trifluoromethylphenyl)siloxane, 12.5 mmol of sodium iodide and 375 mL of acetonitrile were added to a reaction flask, and after stirring, 75 mmol of potassium carbonate and 52.5 mmol of N,N-dimethylallylamine were added. The mixture was reacted at 80° C. for 16 h, filtered, washed with ethyl acetate, and the filtrate was concentrated and dried to obtain a bis(alkenyl) quaternary ammonium salt fluorinated siloxane.
[0044] (5) Under nitrogen atmosphere, deionized water, 3 g initiator ammonium persulfate, 5 g emulsifier sodium dodecylbenzene sulfonate, and 3 g OP-10 were added to a reaction bottle equipped with a dropping funnel and stirred to dissolve; a mixed solution of 100 g glycidyl methacrylate, 20 g ethyl acrylate, 50 g butyl acrylate, 40 g methacrylic acid, and 65 g diene quaternary ammonium salt fluorinated silicone was added to the dropping funnel after mixing, 1 / 3 of the mixed solution was first added dropwise, and the mixture was reacted at 75° C. for 1 h, and then the remaining mixed solution was added dropwise, and the reaction was continued at the same temperature for 2 h. After the reaction was completed, ammonia water was added for neutralization, and finally 0.2 g defoamer BYK-012, 0.3 g wetting dispersant BYK-190, and 0.05 g leveling agent TEGO-A115 were added to obtain a water-based coating for soft stone surface spraying.
[0045] Example 3
[0046] (1) Under nitrogen atmosphere, 15 mmol of dichlorodimethylsilane and 150 mL of toluene were added to a reaction flask. After stirring, 33 mmol of 3-nitro-5-(trifluoromethyl)phenol and 37.5 mmol of sodium hydride were added. The mixture was reacted at 80° C. for 5 h. The mixture was cooled to room temperature, filtered, and recrystallized from toluene and n-hexane to obtain bis(3-nitro-5-trifluoromethylphenyl)siloxane.
[0047] (2) Under a hydrogen atmosphere, 12 mmol of bis(3-nitro-5-trifluoromethylphenyl)siloxane and 180 mL of ethyl acetate were added to a reaction flask, stirred evenly, and then 0.36 mmol of 10% Pd / C was added. The mixture was reacted at 40°C for 12 h, filtered, washed with ethyl acetate, and concentrated under reduced pressure to obtain bis(3-amino-5-trifluoromethylphenyl)siloxane.
[0048] (3) Under a nitrogen atmosphere, 23 mmol of bromoacetic acid, 32 mmol of HATU and 120 mL of N,N-dimethylformamide were added to a reaction flask. After stirring, 10 mmol of bis(3-amino-5-trifluoromethylphenyl)siloxane and 40 mmol of triethylamine were added. The mixture was reacted at 20° C. for 24 h. Ethyl acetate and deionized water were added for extraction. The organic phase was concentrated and dried to obtain bis(3-bromoacetamide-5-trifluoromethylphenyl)siloxane.
[0049] (4) Under nitrogen atmosphere, 8 mmol of bis(3-bromoacetamide-5-trifluoromethylphenyl)siloxane, 6.4 mmol of sodium iodide and 160 mL of acetonitrile were added to a reaction flask, and after stirring, 36 mmol of potassium carbonate and 19.2 mmol of N,N-dimethylallylamine were added. The mixture was reacted at 60° C. for 32 h, filtered, washed with ethyl acetate, and the filtrate was concentrated and dried to obtain a bis(alkenyl) quaternary ammonium salt fluorinated siloxane.
[0050] (5) Under nitrogen atmosphere, deionized water, 5 g initiator ammonium persulfate, 8 g emulsifier sodium dodecylbenzene sulfonate, and 3 g OP-10 were added to a reaction bottle equipped with a dropping funnel and stirred to dissolve; a mixed solution of 100 g glycidyl methacrylate, 15 g ethyl acrylate, 70 g butyl acrylate, 30 g methacrylic acid, and 9 g diene quaternary ammonium salt fluorinated silicone was added to the dropping funnel after mixing, 1 / 3 of the mixed solution was first added dropwise, and the mixture was reacted at 65° C. for 3 h, and then the remaining mixed solution was added dropwise, and the reaction was continued at the same temperature for 4 h. After the reaction was completed, ammonia water was added for neutralization, and finally 0.6 g defoamer BYK-012, 0.1 g wetting dispersant BYK-190, and 0.02 g leveling agent TEGO-A115 were added to obtain a water-based coating for soft stone surface spraying.
[0051] Example 4
[0052] (1) Under nitrogen atmosphere, 80 mmol of dichlorodimethylsilane and 650 mL of toluene were added to a reaction flask. After stirring, 170 mmol of 3-nitro-5-(trifluoromethyl)phenol and 190 mmol of sodium hydride were added. The mixture was reacted at 95° C. for 5 h. The mixture was cooled to room temperature, filtered, and recrystallized from toluene and n-hexane to obtain bis(3-nitro-5-trifluoromethylphenyl)siloxane.
[0053] (2) Under a hydrogen atmosphere, 65 mmol of bis(3-nitro-5-trifluoromethylphenyl)siloxane and 900 mL of ethyl acetate were added to a reaction flask, stirred evenly, and then 1.18 mmol of 10% Pd / C was added. The mixture was reacted at 55° C. for 10 h, filtered, washed with ethyl acetate, and concentrated under reduced pressure to obtain bis(3-amino-5-trifluoromethylphenyl)siloxane.
[0054] (3) Under a nitrogen atmosphere, 110 mmol of bromoacetic acid, 155 mmol of HATU and 525 mL of N,N-dimethylformamide were added to a reaction flask. After stirring, 50 mmol of bis(3-amino-5-trifluoromethylphenyl)siloxane and 190 mmol of triethylamine were added. The mixture was reacted at 30° C. for 15 h. Ethyl acetate and deionized water were added for extraction. The organic phase was concentrated and dried to obtain bis(3-bromoacetamide-5-trifluoromethylphenyl)siloxane.
[0055] (4) Under nitrogen atmosphere, 40 mmol of bis(3-bromoacetamide-5-trifluoromethylphenyl)siloxane, 26 mmol of sodium iodide and 720 mL of acetonitrile were added to a reaction flask, and after stirring, 140 mmol of potassium carbonate and 90 mmol of N,N-dimethylallylamine were added. The mixture was reacted at 65° C. for 24 h, filtered, washed with ethyl acetate, and the filtrate was concentrated and dried to obtain a bis(alkenyl) quaternary ammonium salt fluorinated siloxane.
[0056] (5) Under nitrogen atmosphere, deionized water, 4 g initiator ammonium persulfate, 8 g emulsifier sodium dodecylbenzene sulfonate, and 3 g OP-10 were added to a reaction bottle equipped with a dropping funnel and stirred to dissolve; a mixed solution of 100 g glycidyl methacrylate, 16 g ethyl acrylate, 65 g butyl acrylate, 35 g methacrylic acid, and 12 g diene quaternary ammonium salt fluorinated silicone was added to the dropping funnel after mixing, 1 / 3 of the mixed solution was first added dropwise, and the mixture was reacted at 75° C. for 2 h, and then the remaining mixed solution was added dropwise, and the reaction was continued at the same temperature for 3 h. After the reaction was completed, ammonia water was added for neutralization, and finally 0.5 g defoamer BYK-012, 0.2 g wetting dispersant BYK-190, and 0.1 g leveling agent TEGO-A115 were added to obtain a water-based coating for soft stone surface spraying.
[0057] Example 5
[0058] (1) Under nitrogen atmosphere, 12 mmol of dichlorodimethylsilane and 102 mL of toluene were added to a reaction flask. After stirring, 26 mmol of 3-nitro-5-(trifluoromethyl)phenol and 29.4 mmol of sodium hydride were added. The mixture was reacted at 95° C. for 4 h. The mixture was cooled to room temperature, filtered, and recrystallized from toluene and n-hexane to obtain bis(3-nitro-5-trifluoromethylphenyl)siloxane.
[0059] (2) Under a hydrogen atmosphere, 9 mmol of bis(3-nitro-5-trifluoromethylphenyl)siloxane and 115 mL of ethyl acetate were added to a reaction flask, stirred evenly, and then 0.135 mmol of 10% Pd / C was added. The mixture was reacted at 45°C for 12 h, filtered, washed with ethyl acetate, and concentrated under reduced pressure to obtain bis(3-amino-5-trifluoromethylphenyl)siloxane.
[0060] (3) Under nitrogen atmosphere, 11.2 mmol of bromoacetic acid, 15 mmol of HATU and 55 mL of N,N-dimethylformamide were added to the reaction flask, and after stirring, 5 mmol of bis(3-amino-5-trifluoromethylphenyl)siloxane and 3.5-4 mmol of triethylamine were added, and the mixture was reacted at 20-35° C. for 12-24 h. Ethyl acetate and deionized water were added for extraction, and the organic phase was concentrated and dried to obtain bis(3-bromoacetamide-5-trifluoromethylphenyl)siloxane.
[0061] (4) Under nitrogen atmosphere, 1 mmol of bis(3-bromoacetamide-5-trifluoromethylphenyl)siloxane, 3.6 mmol of sodium iodide and 90 mL of acetonitrile were added to a reaction flask, and after stirring, 18 mmol of potassium carbonate and 11.3 mmol of N,N-dimethylallylamine were added, and the mixture was reacted at 70° C. for 24 h. The mixture was filtered, washed with ethyl acetate, and the filtrate was concentrated and dried to obtain a bis(alkenyl) quaternary ammonium salt fluorinated siloxane.
[0062] (5) Under nitrogen atmosphere, deionized water, 3 g initiator ammonium persulfate, 7 g emulsifier sodium dodecylbenzene sulfonate, and 3 g OP-10 were added to a reaction bottle equipped with a dropping funnel and stirred to dissolve; a mixed solution of 100 g glycidyl methacrylate, 20 g ethyl acrylate, 65 g butyl acrylate, 40 g methacrylic acid, and 15 g diene quaternary ammonium salt fluorinated silicone was added to the dropping funnel after mixing, 1 / 3 of the mixed solution was first added dropwise, and the mixture was reacted at 70° C. for 2 h, and then the remaining mixed solution was added dropwise, and the reaction was continued at the same temperature for 3 h. After the reaction was completed, ammonia water was added for neutralization, and finally 0.6 g defoamer BYK-012, 0.3 g wetting dispersant BYK-190, and 0.2 g leveling agent TEGO-A115 were added to obtain a water-based coating for soft stone surface spraying.
[0063] Comparative Example 1
[0064] (1) Under nitrogen atmosphere, 33 mmol of acrylic acid, 45 mmol of HATU and 150 mL of N,N-dimethylformamide were added to a reaction flask, and after stirring, 15 mmol of bis(3-amino-5-trifluoromethylphenyl)siloxane and 57 mmol of triethylamine were added, and the mixture was reacted at 25° C. for 16 h. Ethyl acetate and deionized water were added for extraction, and the organic phase was concentrated and dried to obtain bis(3-alkenyl-5-trifluoromethylphenyl)siloxane, the structural formula of which is
[0065] (2) Under nitrogen atmosphere, deionized water, 4 g initiator ammonium persulfate, 6 g emulsifier sodium dodecylbenzene sulfonate, and 2.5 g OP-10 were added to a reaction bottle equipped with a dropping funnel and stirred to dissolve; a mixed solution of 100 g glycidyl methacrylate, 18 g ethyl acrylate, 60 g butyl acrylate, 35 g methacrylic acid, and 3 g bis(3-alkenyl-5-trifluoromethylphenyl)siloxane was added to the dropping funnel after mixing, 1 / 3 of the mixed solution was first added dropwise, and the mixture was reacted at 70° C. for 2 h, and then the remaining mixed solution was added dropwise, and the reaction was continued at the same temperature for 3 h. After the reaction was completed, ammonia water was added for neutralization, and finally 0.3 g defoamer BYK-012, 0.2 g wetting dispersant BYK-190, and 0.01 g leveling agent TEGO-A115 were added to obtain a water-based coating for soft stone surface spraying.
[0066] Comparative Example 2
[0067] Under a nitrogen atmosphere, deionized water, 4 g initiator ammonium persulfate, 6 g emulsifier sodium dodecylbenzene sulfonate, and 2.5 g OP-10 were added to a reaction bottle equipped with a dropping funnel and stirred to dissolve; a mixed solution of 100 g glycidyl methacrylate, 18 g ethyl acrylate, 60 g butyl acrylate and 35 g methacrylic acid was added to the dropping funnel after mixing, 1 / 3 of the mixed solution was first added dropwise, and the mixture was reacted at 70°C for 2 h, and then the remaining mixed solution was added dropwise, and the reaction was continued for 3 h at the same temperature. After the reaction was completed, ammonia water was added for neutralization, and finally 0.3 g defoamer BYK-012, 0.2 g wetting dispersant BYK-190 and 0.01 g leveling agent TEGO-A115 were added to obtain a water-based coating for spraying on the surface of soft stone.
[0068] Preparation of adhesive film: Apply water-based paint for soft stone surface spray evenly on 80×80mm qualitative filter paper, apply twice, the paint film thickness is 0.40mm, keep the room clean and dust-free, dry naturally for 48h, and cut the dried filter paper into discs with a radius of 0.50cm.
[0069] Inhibition zone test: Pipette 0.05 mL of 1×10 7 CFU / mL of Escherichia coli suspension was added to the culture dish, beef extract peptone agar medium was added and shaken evenly, then the solidified soft stone surface was sprayed with water-based coating film, placed on the solid culture medium, and cultured in an incubator at a constant temperature of 37°C for 24 hours. After culture, the diameter of the inhibition zone was measured and the average value was taken.
[0070] Table 1 Antibacterial performance test
[0071] Diameter of inhibition zone (mm) Example 1 10.5 Example 2 15.2 Example 3 19.6 Example 4 21.3 Example 5 22.0 Comparative Example 1 - Comparative Example 2 -
[0072] Generally speaking, the larger the diameter of the inhibition zone, the more obvious the antibacterial effect; it can be seen from the test results in the above table that with the increase of the content of the diene quaternary ammonium salt fluorinated silicone, the inhibitory effect of the water-based coating sprayed on the soft stone surface on Escherichia coli is significantly enhanced, and the diameter of the inhibition zone in Example 5 reaches 22.0 mm. This is because the diene quaternary ammonium salt fluorinated silicone contains quaternary ammonium salt groups, which mainly play a bactericidal role, can be adsorbed on the surface of Escherichia coli, penetrate the cell wall, and then combine with the cell membrane, changing the permeability of the Escherichia coli cell membrane, causing the leakage of substances in the bacteria, and finally killing Escherichia coli, achieving the purpose of antibacterial and mildew-proofing; while the comparative examples do not contain quaternary ammonium salt structures and have no antibacterial effect.
[0073] Water absorption test: Weigh 1g of the water-based coating film sprayed on the surface of the cured soft stone, add it to 100mL of deionized water, immerse it in water for 24h, then take out the film and wipe off the residual water on the surface and weigh it, calculate the water absorption, water absorption = (M 吸水后 -M 吸水前 ) / M吸水前 ×100%.
[0074] Surface contact angle test: The water contact angle of the water-based paint film sprayed on the cured soft stone surface is measured by an optical contact angle tester.
[0075] Table 2 Waterproof performance test
[0076] Water absorption (%) Contact angle (°) Example 1 5.2 93.1 Example 2 4.6 106.5 Example 3 4.4 115.3 Example 4 4.1 122.6 Example 5 3.9 128.4 Comparative Example 1 5.3 92.5 Comparative Example 2 10.8 75.2
[0077] It can be seen from the test results in the above table that with the increase of the content of the fluorinated siloxane of the diene quaternary ammonium salt, the waterproof performance of the water-based coating sprayed on the surface of the soft stone is gradually enhanced. The water absorption rate in Example 5 is only 3.9%, and the contact angle is 128.4°. This is because low surface energy substances such as organic fluorine and silicon are introduced into the water-based coating. The bond energy of CF and Si-O bonds is larger than that of CH and CO, and the shielding of the atomic electron cloud on the CC bond is stronger than that of the H atom. Water molecules are difficult to penetrate and a Si-O-Si three-dimensional cross-linked network structure is formed on the coating surface, so that the prepared composite material has a low surface free energy, and a very thin molecular layer can be formed on the surface of the material at the same time, thereby reducing the surface energy, so that water drops cannot stay on the surface, thereby achieving a waterproof effect; organic fluorine and organic silicon are introduced in Comparative Example 1, and its waterproof performance is excellent; Comparative Example 2 does not contain a waterproof group and has poor water resistance.
[0078] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for preparing a water-based coating for spraying on a soft stone surface, characterized in that: The preparation method comprises the following steps: (1) under a nitrogen atmosphere, bis(3-bromoacetamide-5-trifluoromethylphenyl)siloxane, sodium iodide and acetonitrile were added to a reaction flask, and potassium carbonate and N,N-dimethylallylamine were added after stirring. After the reaction was completed, the mixture was filtered, washed with ethyl acetate, and the filtrate was concentrated and dried to obtain a bis-alkenyl quaternary ammonium salt fluorinated siloxane; (2) Under nitrogen atmosphere, deionized water, 3-5 g initiator ammonium persulfate, 5-8 g emulsifier sodium dodecylbenzene sulfonate, and 2-3 g OP-10 were added to a reaction bottle equipped with a dropping funnel, and stirred to dissolve; a mixed solution of 100 g glycidyl methacrylate, 15-20 g ethyl acrylate, 50-70 g butyl acrylate, 30-40 g methacrylic acid, and 3-15 g diene quaternary ammonium salt fluorinated silicone was added to the dropping funnel after mixing, 1 / 3 of the mixed solution was first added dropwise, and the mixture was reacted at 65-75° C. for 1-3 h, and then the remaining mixed solution was added dropwise, and the reaction was continued at the same temperature for 2-4 h. After the reaction was completed, ammonia water was added for neutralization, and finally 0.2-0.6 g defoamer, 0.1-0.3 g wetting dispersant, and 0.05-0.2 g leveling agent were added to obtain a water-based coating for soft stone surface spraying.
2. The method for preparing a water-based coating for spraying on a soft stone surface according to claim 1, characterized in that: In the step (1), the ratio of bis(3-bromoacetamide-5-trifluoromethylphenyl)siloxane, sodium iodide, potassium carbonate and N,N-dimethylallylamine is 1 mol:(0.5-0.8) mol:(3-4.5) mol:(2.1-2.4) mol.
3. The method for preparing a water-based coating for spraying on a soft stone surface according to claim 1, characterized in that: In the step (1), the reaction temperature is 60-80° C. and the reaction time is 16-32 h.
4. The method for preparing a water-based coating for spraying on a soft stone surface according to claim 1, characterized in that: The preparation method of bis(3-bromoacetamide-5-trifluoromethylphenyl)siloxane in step (1) comprises the following steps: S1. Under a nitrogen atmosphere, add dichlorodimethylsilane and toluene to a reaction flask, stir evenly, then add 3-nitro-5-(trifluoromethyl)phenol and sodium hydride, stir to react, and after the reaction is completed, cool to room temperature, filter, and recrystallize from toluene and n-hexane to obtain bis(3-nitro-5-trifluoromethylphenyl)siloxane; S2. Under a hydrogen atmosphere, add bis(3-nitro-5-trifluoromethylphenyl)siloxane and ethyl acetate to a reaction flask, stir evenly, add 10% Pd / C by mass, react at 40-60° C. for 5-12 h, filter, wash with ethyl acetate, and concentrate under reduced pressure to obtain bis(3-amino-5-trifluoromethylphenyl)siloxane; S3. Under a nitrogen atmosphere, add bromoacetic acid, HATU and N,N-dimethylformamide to a reaction flask, stir evenly, then add bis(3-amino-5-trifluoromethylphenyl)siloxane and triethylamine, react at 20-35°C for 12-24h, add ethyl acetate and deionized water for extraction, concentrate the organic phase, and dry to obtain bis(3-bromoacetamide-5-trifluoromethylphenyl)siloxane.
5. The method for preparing a water-based coating for spraying on a soft stone surface according to claim 4, characterized in that: In the step S1, the ratio of dichlorodimethylsilane, 3-nitro-5-(trifluoromethyl)phenol and sodium hydride is 1 mol:(2.05-2.2) mol:(2.3-2.5) mol.
6. The method for preparing a water-based coating for spraying on a soft stone surface according to claim 4, characterized in that: In step S1, the reaction temperature is 80-100° C. and the reaction time is 2-5 h.
7. The method for preparing a water-based coating for spraying on a soft stone surface according to claim 4, characterized in that: In the step S2, the ratio of bis(3-nitro-5-trifluoromethylphenyl)siloxane to Pd / C is 1 mol:(0.01-0.03) mol.
8. The method for preparing a water-based coating for spraying on a soft stone surface according to claim 4, characterized in that: In the step S3, the ratio of bromoacetic acid, HATU, bis(3-amino-5-trifluoromethylphenyl)siloxane and triethylamine is (2.1-2.3) mol: (2.8-3.2) mol: 1 mol: (3.5-4) mol.
9. A process for spraying a water-based paint obtained by the preparation method according to any one of claims 1 to 8 on a soft stone surface, characterized in that: The spraying process is: soft stone degreasing - alcohol washing - water washing - sandblasting - spraying water-based paint - curing.
10. The process for spraying water-based paint on the surface of soft stone according to claim 9, characterized in that: The curing temperature is 70-90°C.
Citation Information
Patent Citations
An antibacterial, low surface energy marine antifouling coating composition
CN105199577B
High-performance low-cost microlite coating and preparation method thereof
CN117777807A
Quaternary ammonium salt-fluorosilicone acrylate block copolymer as well as preparation method and application thereof to antibacterial coating material
CN104177573A
Waterborne antibacterial coating
CN108727928A
